Embouchure dystonia: a video guide to diagnosis and evaluation. Issue 1 (December 2016) - Frucht, Steven
Abstract Background Embouchure dystonia is an unusual focal task-specific dystonia affecting the muscles that control the flow of air into the mouthpiece of a brass or woodwind instrument. The complexity of the embouchure and the relative rarity of the condition pose barriers for recognition and management of the disorder. Methods Case review and video survey. Results This paper presents four video compilations that illustrate the rich phenomenology of embouchure dystonia, in order to enhance recognition and diagnosis. Conclusion The phenomenology of embouchure dystonia is discussed.